Silkworm cocoon (Bombyx mori) accelerates wound healing in skin excision: a study on macrophage and VEGF - Sudirman, Sudirman; Hasan, Cahya Yustisia; Arindra, Pingky Krisna (Faculty of Dentistry, Universitas Gadjah Mada, 2024)
Silkworm cocoon (Bombyx mori) is a natural polymer composite and largely used as bio-functional material for wound healing. It consists of fibroin and sericin protein that has antibacterial effect. This study aimed to investigate the effect of silkworm cocoons (Bombyx mori) wound dressing on the number of macrophages and VEGF expression in skin excision. The subject of this study was 12 Wistar rats, which were grouped based on the duration of wound dressing application (3rd day and 6th day) and the use of dressing materials (n = 6). The rats were anesthetized with ketamin and xylazine prior to wound excision. A punch biopsy wound excision with 4 mm diameter of subcutaneous depth was made on both sides of the rat’s back, with the right side dressed with silkworm cocoon as the treatment group and the left side dressed with moist gauze application as the control group. Hematoxylin-eosin (HE) staining was performed to observe the number of macrophage cells. Immunohistochemical staining using an anti-VEGF antibody was performed to observe the expression of VEGF. Data were analyzed using a two-way ANOVA and an Independent t-test with confidence interval of 95%. Statistical analysis demonstrated a significantly higher number of macrophages in the silkworm cocoon wound dressing group on 6 days post-application (p = 0.026) and significantly higher VEGF expression in the silkworm cocoon wound dressing group on 3 days post-application (p = 0.002) and on 6 days post-application (p = 0.044). Silkworm cocoon (Bombyx mori) wound dressing can increase the number of macrophages and VEGF expression in wound excision model in Wistar rat.